2016
DOI: 10.1016/j.gaitpost.2016.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of leg muscle fatigue on gait in patients with Parkinson's disease and controls with high and low levels of daily physical activity

Abstract: Patients with Parkinson's disease (PD) are more susceptible to muscle fatigue, which can damage their gait. Physical activity can improve muscle condition, which is an important aspect during walking. The aim of this study was to analyze the effects of lower limb muscle fatigue on gait in patients with PD and healthy individuals, grouped according to physical activity level. Twenty Patients with PD (PD group) and 20 matched individuals (control group) were distributed according to physical activity level into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 31 publications
3
37
1
6
Order By: Relevance
“…Given the strong correlation between arm swing and stride amplitude (44), spontaneous overflow from one parameter to the other may also have occurred. Recent work also showed a significant increase in stride length following a repeated sit-to-stand protocol in both PD and age-matched HE (45). These effects, not demonstrated during short gait trials in gait laboratories, support the European guideline’s recommendation to undertake 30 min bouts of brisk walking as a rehabilitation strategy for PD (21).…”
Section: Discussionmentioning
confidence: 93%
“…Given the strong correlation between arm swing and stride amplitude (44), spontaneous overflow from one parameter to the other may also have occurred. Recent work also showed a significant increase in stride length following a repeated sit-to-stand protocol in both PD and age-matched HE (45). These effects, not demonstrated during short gait trials in gait laboratories, support the European guideline’s recommendation to undertake 30 min bouts of brisk walking as a rehabilitation strategy for PD (21).…”
Section: Discussionmentioning
confidence: 93%
“…Nonetheless, the underlying pathophysiologic mechanisms that potentially contribute to these blunted responses in patients with PD are still not fully understood. This becomes important because exercise is frequently employed as a coping resource to manage quality of life, motor function, physical capacity, fatigue perception, and disease progression of PD (Allen et al 2017;David et al 2016;Kelly et al 2014;Krumpolec et al 2017;Santos et al 2016;Silva-Batista et al 2018;Silveira et al 2018;Zhou et al 2017). Importantly, the abnormal responses to exercise could make exercise prescription more difficult to be managed to some patients with PD.…”
Section: Introductionmentioning
confidence: 99%
“…27 . Few studies investigated the impact of fatigue on mobility and walking capacity in individuals with PD 11,28,29 . Our results showed that patients with higher scores of PFS16 had worse performance in a basic mobility skill (TUG), gait speed over a short distance (10MWT), and endurance and ability to walk over longer distances (6MWT).…”
Section: Discussionmentioning
confidence: 99%